EXPLORING THE IMPACT OF SOCIAL CAPITAL ON ENTREPRENEURIAL ORIENTATION AND BUSINESS PERFORMANCE (Study on Members of MSMEs Communities in Malang) - Yudha, Prakasa (Profit: Jurnal Adminsitrasi Bisnis, 2018)
This research analyzes the relationship between social capital and business performance with entrepreneurship orientation as an intermediary variable. This research was conducted in 4 (four) communities of micro, small and medium enterprises (MSMEs) in Malang city with a population of 324 business actors. Proportional Cluster Random Sampling technique was applied, involving 90 respondents who are members of the MSMEs community. The data was gathered through questionnaires. The findings showed that social capital significantly affects entrepreneurial orientation as well as business performance. It is also found that Entrepreneurship Orientation has a significant influence on Business Performance. Lastly, it is found that the effect of Social Capital on Business Performance was mediated byÂ  Entrepreneurial Orientation.Â Â